AGB star atmospheres modeling as feedback to stellar evolutionary and galaxy models. Issue Volume 14:Issue S343(2019) (August 2018) - Rau, Gioia; Wittkowski, M.; Chiavassa, A.; Carpenter, K.; Nielsen, K.; Airapetian, V. S.
Abstract: The chemical enrichment of the Universe is considerably affected by the contribution of cool evolved stars. We studied the O-rich star R Peg and the C-rich star V Oph, using respectively the VLTI/GRAVITY and VLTI/MIDI instruments. We interpret the data using grids of 1-D and 3-D dynamic model atmospheres.